Chemical composition, antioxidant activity and bioaccessibility studies in phenolic extracts of two Hericium wild edible species - Heleno, Sandrina A. (2015)
Mushrooms are rich sources of bioactive compounds such as phenolic acids. When ingested, these molecules have to be released from the matrix to be transformed/absorbed by the organism, so that they can exert their bioactivity. Several in vitro methodologies have been developed in order to evaluate the bioavailability of bioactive compounds. Herein, two Hericium species were analyzed for their chemical composition and antioxidant activity. Furthermore, an in vitro digestion of the mushrooms and mushroom phenolic extracts was performed, and the digested samples were also submitted to antioxidant activity evaluation in order to evaluate the bioaccessibility of the phenolic acids identified in the samples. Hericium species showed similar chemical profiles (except for tocopherols), varying only in the concentration of the compounds. The phenolic extracts revealed higher antioxidant activity than the in vitro digested samples, meaning that this process decrease the antioxidant properties of the extract/mushroom. Nevertheless, phenolic acids were found in the digested samples, meaning that those molecules are bioaccessible.